Greenwashing memberikan Pengaruh Pada Niat Beli Hijau yang dimediasi Word of Mouth: Perspektif Theory of Planned Behaviour - Sella Ayu Pratiwi; Dimas Wibisono (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2025)
Greenwashing has a negative impact on the environment and will certainly have an effect on consumer doubts in consuming environmentally friendly products. The purpose of this study is to test the effect of greenwashing on green purchase intention with word of mouth as a mediating variable by integrating specific components of the Theory of Planned Behavior This type of research is quantitative research with a research design in the form of a causal study and using a survey research form. The population of this study includes active students at the Faculty of Economics and Business (FEB) of Alma Ata University who understand environmentally friendly products. The data used are primary data with a sample size of 150. Sample selection using probability sampling and nonprobability sampling methods with non-probability sampling techniques by purposive sampling. Data analysis was carried out using SEM-PLS. The results of the nature of the mediating variable partial mediation in other words, whether or not there is a mediating variable word of mouth, greenwashing has a positive and significant effect on green purchase intention. Keywords: Greenwashing, Green Purchase Intention, Word of Mouth, Theory of Planned Behavior, Environmental Marketing